Emergence and Mechanism of Resistance of Tulathromycin Against Mycoplasma hyopneumoniae in a PK/PD Model and the Fitness Costs of 23S rRNA Mutants - Xia, Xirui; Yang, Lan; Ling, Yuzhou; Yu, Jiao; Ding, Huanzhong (Frontiers in Veterinary Science, 2022)
Macrolides are widely used in diseases caused by Mycoplasma spp. The new semi-synthetic macrolide antibiotic tulathromycin is currently in wide use for the treatment of respiratory diseases of livestock. The objective of this study was to evaluate the antibacterial effect of tulathromycin against Mycoplasma hyopneumoniae using an in vitro pharmacokinetic/pharmacodynamic (PK/PD) model to reveal mechanisms of antibiotic resistance and to evaluate the fitness of drug-resistant strains. In this study, high performance liquid chromatography-tandem mass spectrometry was used to determine drug concentrations for the in vitro model after dosing in the range 0.3125 - 20 mg /L. The ratio of the area under the concentration-time curve (AUC) over 72 h divided by the MIC (AUC72h/MIC) had the highest correlation with the antibacterial effect of tulathromycin against M. hyopneumoniae. Tulathromycin also showed concentration-dependent antimicrobial effects and promoted the emergence of drug-resistant bacteria after being cultured for 168 h and most were mutations in 23S rRNA at site A2058G (E.coli numbering) and only a single isolate was an A2058T(E.coli numbering) mutant. In the presence of reserpine, we determined the MIC of tulathromycin, tilmicosin, tiamulin and tylosin against these drug-resistant bacteria and the strains with efflux pump mechanisms were found among the strains resistant to tilmicosin. Gene expression analysis indicated that the ABC and MATE transporter efflux pump genes RS01935, RS02670, RS01115, RS01970, RS02395 and RS03540 were up-regulated in the three strains (P<0.05 or P<0.01). These investigations provide guidance for clinical administration of tulathromycin and elucidate the mechanism and fitness cost of drug resistance in M. hyopneumoniae.